Епістолярний діалог Володимира Винниченка з Розалією Ліфшиць (1911–1918) (завершення) - Миронець, Н. (Слово і Час, 2010)
Закінчення. Див.: СіЧ. – 2007. – №№9–10; 2008. – №№1, 3, 6–8; 2009. – №№2, 4, 6, 12; 2010. – №№1–3.